Research trends on learning mathematics with the CPA (Concrete-Pictorial-Abstract) approach - Lutfi, Jasmine Salsabila; Dasari, Dadan (PRISMA, 2024)
Learning mathematics with the CPA approach has been practiced in Singapore and proven its effectiveness. However, there needs to be a synthesis of previous studies to find research gaps for future research. This article is a preliminary-research for information on the CPA approach and its modifications to mathematical abilities and attitudes. This article is a Systematic Literature Review (SLR) of 39 studies published from 2010 to April 2023 using the Publish or Perish application with the Scopus database. This article aims to find out: (1) Description of mathematics education research trends using the CPA approach in terms of publication year, author, country, level of education, and mathematics content. (2) Application of the CPA approach to the type of mathematical ability and attitude of students. The results showed that research outside the elementary school level needs further investigation. Abstract mathematical concepts require a CPA approach. The CPA approach has a positive effect on students with or without learning disabilities or at risk of failure. Results and suggestions for future research on this topic are provided.